Digital Diplomacy: A Case Study of Foreign Relations of Mongolian and India in Social Media by Big Data Analysis and Computation - Shinetsetseg Jargalsaikhan; Shu-Chin Huang; I-Tung Shih (Engineering Proceedings)
We explored digital diplomacy, an evolving field, focusing on the digital engagement strategies of India and Mongolia from 2012 to 2022 through a quantitative analysis of secondary data sourced from social media platforms. We investigated how these countries utilized digital tools to shape their international relations, highlighting the impact of digital diplomacy on traditional diplomatic practices and the potential for enhancing public diplomacy. By examining parameters such as post frequency and engagement rates, significant differences were determined to suggest strategic improvements for Mongolia. The findings offer the basis for the adoption of digital diplomacy, emphasizing its role in reshaping global interactions in the digital era.